Copper‐Catalyzed 1, 4‐Addition of a Silicon Nucleophile to Azadienes. Issue 16 (30th March 2023) - Chu, Wen‐Dao; Wang, Chun‐Mei; Zhan, Jie; Zeng, Ya‐Li; Liu, Yong; Chen, Bo; Zhang, Kaiming; He, Cheng‐Yu; Liu, Quan‐Zhong
Abstract: Copper‐catalyzed 1, 4‐addition of a silicon nucleophile to azadienes is reported. This method facilely provided a wide variety of dibenzylic silane derivatives in good to excellent yields. The important practical features are the use of a cheap catalytic system, mild reaction conditions, and broad substrate scope. Abstract : Here developed a copper‐catalyzed 1, 4‐addition of a silicon nucleophile to azadienes This method facilely provided a wide variety of dibenzylic silane derivatives in good to excellent yields.